2018
DOI: 10.1016/j.jcmgh.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Deletion in the Endothelium, but Not in the Epithelium, Protects From Radiation-Induced Enteritis

Abstract: Background & AimsRadiation therapy in the pelvic area is associated with side effects that impact the quality of life of cancer survivors. Interestingly, the gastrointestinal tract is able to adapt to significant changes in oxygen availability, suggesting that mechanisms related to hypoxia sensing help preserve tissue integrity in this organ. However, hypoxia-inducible factor (HIF)-dependent responses to radiation-induced gut toxicity are unknown. Radiation-induced intestinal toxicity is a complex process invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…98 Recently, it has been shown that endothelial hypoxia-inducible factor (HIF)−1α deletion confers resistance to radiation-induced enteritis, whereas similar deletion in intestinal epithelium does not, suggesting new functions of endothelial HIF-1α-signalling pathways as mediators of mucosal-inflammatory processes. 99 On the other hand, it has been demonstrated in vivo that the endothelium is directly involved in the progression of radiation-induced enteritis by using a mouse model harbouring an endothelium-specific deletion of the serpinE1 gene, which encodes the plasminogen activator inhibitor-type 1 (PAI-1). 100…”
Section: Endothelial Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…98 Recently, it has been shown that endothelial hypoxia-inducible factor (HIF)−1α deletion confers resistance to radiation-induced enteritis, whereas similar deletion in intestinal epithelium does not, suggesting new functions of endothelial HIF-1α-signalling pathways as mediators of mucosal-inflammatory processes. 99 On the other hand, it has been demonstrated in vivo that the endothelium is directly involved in the progression of radiation-induced enteritis by using a mouse model harbouring an endothelium-specific deletion of the serpinE1 gene, which encodes the plasminogen activator inhibitor-type 1 (PAI-1). 100…”
Section: Endothelial Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…Whilst epithelium-specific HIF-1α deletion has no effect upon radiation-induced enteritis, mice with endothelium-specific HIF-1α deletions present with reduced intestinal damage 64 . HIF-1α is known to contribute to the pathology of pulmonary hypertension 65,66 , with some work specifically interrogating endothelial HIF signalling 67 .…”
Section: Discussionmentioning
confidence: 97%
“…HIF-1α is more readily found in the mouse bleomycin model of PF raising the question of differences between the two species and insults (77). Whilst epithelium-specific HIF-1α deletion has no effect upon radiation-induced enteritis, mice with endothelium-specific HIF-1α deletions present with reduced intestinal damage (78). HIF-1α is known to contribute to the pathology of pulmonary hypertension (79,80), with some work specifically interrogating endothelial HIF signaling (81).…”
Section: Discussionmentioning
confidence: 99%